Third Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 12-17, 1989. Day 4. Plenary session. Tape 1 of 2 - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1989)
"In order to better understand how readers comprehend text, we have studied how they think while reading. We present evidence on the thinking of good and poor readers and show that the quality of the thinking strategies they employ markedly distinguishes one from the other. This evidence shows that reading well is really a species of thinking well -- the two cannot be separated. Good readers are good because they use productive thinking strategies and avoid counterproductive ones. We will discuss some of the implications of this conclusion for literacy development." (abstract from workshop proceedings) No audio